Valorization of lignocellulosic fibers in the development of composite materials - DAIRI, Badrina (Biopolymer Applications Journal, 2024)
Natural fibers have recently attracted the attention of scientists because of their low-cost, low-density, renewable, biodegradable and non-abrasive properties. The growing use of composite materials is giving rise to problems of waste management. As a result, there is a growing trend towards the use of biodegradable products, either by using biodegradable polymers, or by incorporating biodegradable fibers into polymeric materials. In this context, various high-density polyethylene-based formulations have been prepared (HDPE/Wood Flour, HDPE/Wheat Bran, and HDPE/Wood Flour/Wheat Bran). The various composites were initially blended in a calender before the various samples, with average thicknesses of 2 and 3 mm, were prepared by compression at 190°C and characterized by mechanical test.